Featured Cover. Issue 4 (10th April 2023) - Willows, Jake W.; Robinson, Morganne; Alshahal, Zahra; Morrison, Samantha K.; Mishra, Gargi; Cyr, Harrison; Blaszkiewicz, Magdalena; Gunsch, Gilian; DiPietro, Sabrina; Paradie, Emma; Tero, Benjamin; Harrington, Anne; et al.
Abstract : Cover legend: The cover image is based on the Research Article Age‐related changes to adipose tissue and peripheral neuropathy in genetically diverse HET3 mice differ by sex and are not mitigated by rapamycin longevity treatment by Jake W. Willows et al., https://doi.org/10.1111/acel.13784 .